A Survey on Ontology Tools in Semantic Web - Karpagam, P (International Journal of Computer Sciences and Engineering, 2025)
The linguistics internet will be thought of as a mesh of connected data (resources) or a globally connected distributed information [4, 5, 7]. the most goal is that information ought to simply be processed by machines. Ontology tools will be applicable for all stages of the metaphysics lifecycle (creation, population, validation, deployment, maintenance and evolution). metaphysics will be accustomed support varied data management together with data retrieval, store and sharing. There ar many metaphysics languages like XML, RDF(S), DAML+OIL and bird of prey. several metaphysics tools are developed for implementing information of metaphysics victimisation these languages. However, current metaphysics tools have some issues in interoperation and cooperative work. the first goal of this survey is to grasp and measure every tool by analyzing and victimisation them. Therefore, we will develop the new generation tool not solely supporting a lot of capabilities, however additionally determination current tools’ issues